Oleic acid as potential immunostimulant in metabolism pathways of hybrid grouper fingerlings (Epinephelus fuscoguttatus× Epinephelus lanceolatus) infected with Vibrio vulnificus - Natnan, Maya Erna; Low, Chen-Fei; Chong, Chou-Min; Bunawan, Hamidun; Baharum, Syarul Nataqain (Nature Publishing Group, 2023)
Grouper culture has been expanding in Malaysia due to the huge demand locally and globally. However, due to infectious diseases such as vibriosis, the fish mortality rate increased, which has affected the production of grouper. Therefore, this study focuses on the metabolic profiling of surviving infected grouper fed with different formulations of fatty acid diets that acted as immunostimulants for the fish to achieve desirable growth and health performance. After a six-week feeding trial and one-week post-bacterial challenge, the surviving infected grouper was sampled for GC–MS analysis. For metabolite extraction, a methanol/chloroform/water (2:2:1.8) extraction method was applied to the immune organs (spleen and liver) of surviving infected grouper. The distribution patterns of metabolites between experimental groups were then analyzed using a metabolomics platform. A total of 50 and 81 metabolites were putatively identified from the spleen and liver samples, respectively. Our further analysis identified glycine, serine, and threonine metabolism, and alanine, aspartate and glutamate metabolism had the most impacted pathways, respectively, in spleen and liver samples from surviving infected grouper. The metabolites that were highly abundant in the spleen found in these pathways were glycine (20.9), l-threonine (1.0) and l-serine (0.8). Meanwhile, in the liver l-glutamine (1.8) and aspartic acid (0.6) were found to be highly abundant. Interestingly, among the fish diet groups, grouper fed with oleic acid diet produced more metabolites with a higher percent area compared to the control diets. The results obtained from this study elucidate the use of oleic acid as an immunostimulant in fish feed formulation affects more various immune-related metabolites than other formulated feed diets for vibriosis infected grouper.